UPAYA MENINGKATKAN HIGHER ORDER THINKING SKILL (HOTS) SISWA MENGGUNAKAN METODE INQUIRY PADA MATERI BILANGAN BULAT - Trinanda Anugrah Tambun; Wirna Arifitriana; Erwina Azizah Hasibuan (JURNAL MathEdu (Mathematic Education Journal), 2021)
The objectives of this study include: first: To determine the increase in students' HOTS levels using the Inquiry method on the subject of integer operations. Second: To find out the increase in student learning outcomes by using the Inquiry method on the subject of integer operations. Third: To find out the increase in the ability of teachers to manage learning by using the Inquiry method on the subject of integer operations. This type of research is Classroom Action Research (CAR). Which consists of 2 cycles. The subject of this research is class V SDN No. 200205 South Padangsidimpuan, totaling 20 students. The object of this research is the application of the Inquiry learning model, which aims to improve students' mathematical problem solving abilities. The results showed that the ability of student learning outcomes in learning mathematics through the Inquiry method with the percentage of student learning test results in mathematics, namely 40% with the "Enough" category in the first cycle to 85% with the "Good" category in the second cycle. Meanwhile, the results of the observation of the teacher's ability in the first cycle obtained a score of 79% in the "Good Enough" category to 86% with the "Good" category in the second cycle.